2015
DOI: 10.1016/j.devcel.2014.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Formin-Mediated Actin Polymerization at Endothelial Junctions Is Required for Vessel Lumen Formation and Stabilization

Abstract: During blood vessel formation, endothelial cells (ECs) establish cell-cell junctions and rearrange to form multicellular tubes. Here, we show that during lumen formation, the actin nucleator and elongation factor, formin-like 3 (fmnl3), localizes to EC junctions, where filamentous actin (F-actin) cables assemble. Fluorescent actin reporters and fluorescence recovery after photobleaching experiments in zebrafish embryos identified a pool of dynamic F-actin with high turnover at EC junctions in vessels. Knockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 44 publications
(54 reference statements)
1
66
2
Order By: Relevance
“…Studies in diverse vertebrate cell types in vitro and in vivo demonstrate a key role for formins in coordinating apical surface formation among groups of cells during epithelial lumen formation (Grikscheit et al, 2015;Madrid et al, 2010;Phng et al, 2015;Taniguchi et al, 2015). Likewise, our data here and in previous work (Sedzinski et al, 2016) demonstrate a similar requirement for formins in the emergence of an individual apical epithelial surface in MCCs.…”
Section: Discussionsupporting
confidence: 72%
“…Studies in diverse vertebrate cell types in vitro and in vivo demonstrate a key role for formins in coordinating apical surface formation among groups of cells during epithelial lumen formation (Grikscheit et al, 2015;Madrid et al, 2010;Phng et al, 2015;Taniguchi et al, 2015). Likewise, our data here and in previous work (Sedzinski et al, 2016) demonstrate a similar requirement for formins in the emergence of an individual apical epithelial surface in MCCs.…”
Section: Discussionsupporting
confidence: 72%
“…In summary, although Mogat1 expression is highly upregulated in fatty livers of lipodystrophic ( Agpat2 Ϫ / Ϫ ) and ob / ob oligonucleotide approaches in an acute experimental setting bring about reduced liver TAG and improved IR and type 2 diabetes mellitus . A recent study, although not related to the metabolic studies discussed here, reported that the use of antisense technology and genetic deletion resulted in widely different phenotypes (33)(34)(35). We interpret our study with an additional caution.…”
Section: Mogat1contrasting
confidence: 40%
“…However, unlike well-studied actin networks such as lamellipodia, we know almost nothing about the molecular control of MCC apical actin assembly. We therefore sought to characterize the dynamics of this actin population, which can be done by quantifying the turnover of apical actin in MCCs using fluorescence recovery after photobleaching (FRAP) of YFP-actin (Fritzsche et al, 2013;Grikscheit et al, 2015;Phng et al, 2015;Sahasrabudhe et al, 2016). We photobleached a small region of interest within a medial portion of MCC apical domains and monitored subsequent recovery of YFP-actin fluorescence (Fig.…”
Section: Rhoa Controls the Dynamics Of MCC Apical Emergencementioning
confidence: 99%